Youth in livestock, the engine for change: strategic partnerships with a private company (CIAT/CCAFS-Alqueria): The beginnings, incentives, and objectives of the Herederos de Tradición (Heirs of Tradition) initiative carried out by Alquería’s farmer training programs. - Triana Ángel, Natalia; Ariza Aya, Mauricio (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2019)
In 2012, the private dairy company Alquería launched its first pilot training program for small-scale milk producers, MACA. The name MACA derives from the pilot’s initial test region in the municipalities near the Macarena mountain range in El Meta, Colombia. This particular area has been identified for the urgent need to tackle the low rates of schooling of its producers, and the need for a technification of the livestock farms to increase their productivity and, in turn, the quality of life of their managers. En el año 2012, la empresa privada de lácteos Alquería lanzó su primer programa piloto de capacitación a pequeños productores de leche: MACA. Así se le bautizó en ese momento pues la zona de prueba inicial del piloto fue en los municipios cercanos a la serranía de la Macarena en el Meta, Colombia; respondiendo a lo que se venía identificando como una necesidad urgente en esa zona en particular, el atajar los bajos índices de escolaridad de los productores e impulsar la tecnificación de los predios ganaderos con el ánimo de incrementar su productividad y, con esta, la calidad de vida de quienes los administran.